A Case of Fulminant Type Community-Acquired Pneumonia Found to be Caused by Pseudomonas aeruginosa at Autopsy - Furumido, Mina; Takamura, Kei; Nakakubo, Sho; Kikuchi, Hajime; Yamamoto, Makoto; Kikuchi, Keisuke (Archives of Clinical and Medical Case Reports, 2019)
The present case involved a 27-year-old woman, who presented to a nearby physician with chief complaints of fever and dyspnea and hospitalized with a diagnosis of right lobar pneumonia on the same day. The patient was treated with antibiotics (aminobenzylpenicillin/sulbactam); however, exacerbation of respiratory status occurred with hypotension, and she was transferred to the authors’ hospital under tracheal intubation. The right superior lobe exhibited a wide range of infiltrative shadows with air bronchograms. Vasopressor and continuous hemodiafiltration were initiated to address overall exacerbation, and antibiotics (ciprofloxacin) were added. However, ventilation could not be maintained due to the large quantity of respiratory secretions; consequently, extracorporeal membrane oxygenation (ECMO) was initiated 5 h after admission to the intensive care unit. Due to the large quantity of Gram-negative bacilli confirmed by gram stain of respiratory secretions, amikacin was added. Although oxygenation was improved after initial ECMO induction, the patient died on day 2 of admission, despite being revived from sudden cardiac arrest. Pseudomonas aeruginosa was detected in respiratory secretions, blood cultures, and all lung tissues at autopsy, and the illness was believed to be a fulminant form of community-acquired pneumonia caused by the organism. This is a rare case and autopsy finding and, as such, contributes to the scarce literature.